Sufisme Perkotaan: Fenomenologi Kebangkitan Spiritualitas Majlis Taklim Al Hikam di Surabaya - Mahfudin, Agus; Safik, Abduloh (Proceedings of Annual Conference for Muslim Scholars, 2022)
Departing from an urban community which incidentally is a modern society, call it the city of Surabaya, as a modern society, of course, cannot be separated from the sophistication of technology that is all young and efficient, the dynamics of which are accelerating where globalization is moving very rapidly, so that people forget As a result of the luxurious, hedonistic lifestyle that is rife in the Surabaya environment, several community groups are finally looking for an atmosphere that forms their spiritual calm, many classes of society following recitations with Sufism nuances, its existence is widely found in mosques, religious institutions in the Surabaya environment, therefore an interesting phenomenon related to the Awakening of Spirituality in Surabaya. This study uses a Qualitative-Descriptive Research methodology with a participant phenomenology approach, exploring and observing their attitudes and perspectives in navigating life in today's modern era. A contribution of this research is to be able to provide an immunity to institutions, both formal and non-formal, especially in urban communities